2009
DOI: 10.1080/08860220902928981
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation of MSC into Cells with a Renal Tubular Epithelial-Like Phenotype

Abstract: Bone marrow mesenchymal stem (stromal) cells (MSCs) are shown to differentiate into different renal lineages in in vivo injury models. Nevertheless, the in vitro differentiation of MSCs into a renal tubular epithelial lineage has not been investigated. We hypothesize that the injured renal epithelial cells express renotypic factors that may influence the differentiation of MSCs into a renal tubular epithelial lineage. MSCs were cocultured for up to seven days with injured or uninjured murine cortical tubular r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 49 publications
0
39
0
Order By: Relevance
“…The reason is that differentiation of BM-MSCs needs stimulation from the cytokines secreted by damaged visceral organs. However, these cytokines are not secreted by the normal kidney tissues (Singaravelu and Padanilam, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that differentiation of BM-MSCs needs stimulation from the cytokines secreted by damaged visceral organs. However, these cytokines are not secreted by the normal kidney tissues (Singaravelu and Padanilam, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The role of cytokines in organ I/R injury has gained increased attention as a result of many studies on the cytokine network. BM-MSCs possess powerful secretory functions, which assist in AKI repair through their paracrine effect (Di Nicola et al, 2002;Singaravelu and Padanilam, 2009). In the present study, the supernatant of mBM-MSCs grown in low-sugar DMEM was found to contain the cytokines BMP-7, HGF, and VEGF, all of which can facilitate the repair of renal injury (Hruska, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Because vimentin is usually not expressed in differentiated tubular cells, the stable expression of this marker (Figure 2, D and H) in our culture highlights that these cells are not fully differentiated and that they are closer to progenitor cells. At day 21, we detected the expression of cadherin-16/KSP by real-time PCR ( Figure 2F) and immunofluorescence analysis 24 ( Figure 2I). Cadherin-16 is expressed specifically in renal tubular cells, and in vivo its expression starts at the S-shaped body stage, around E14.5 in mice.…”
Section: Gpscs Differentiate Into Renal Tubular Cells In Vitromentioning
confidence: 99%
“…MSC therapy reportedly ameliorates kidney injury, accelerates tubule proliferation, and restores renal function. 4,5 However, many difficulties must be overcome to successfully implement MSC therapy, one of which is the scarcity of MSCs in injured tissues after systematic infusion. [6][7][8] The insufficient homing of MSCs and the inability to drive them to the damaged kidney tissues have become a major barrier to the effective implementation of MSC therapy.…”
Section: Introductionmentioning
confidence: 99%